Delayed Cord Clamping and Umbilical Cord Milking among Infants in California Neonatal Intensive Care Units - Tran, Chinh L.; Parucha, Janella M.; Jegatheesan, Priya; Lee, Henry C. (American Journal of Perinatology, 2020)
Objective To assess the current practice of delayed cord clamping (DCC) and to determine patient and hospital factors that predict DCC.Study Design The California Perinatal Quality Care Collaborative (CPQCC) collects data on preterm and acutely ill infants. In 2016, 52 CPQCC neonatal intensive care units (NICUs) collected data on DCC. Hospital and patient characteristics were analyzed using multivariable logistic regression.Results Of 5,332 deliveries, 1,555 (29%) newborns received DCC. Hospital rates ranged from 0 to 74.5% and increased from 21 to 37% throughout 2016. Infants delivered at <32 weeks or with birth weight <1,500 g were more likely to receive DCC (odds ratio: 2.80; 95% confidence interval: 2.33, 3.36). Cesarean delivery was associated with less likelihood of DCC (odds ratio: 0.68; 95% confidence interval: 0.59, 0.79). After risk adjustment, 17 (33%) hospitals had higher than expected DCC rate. Hospitals with less than 50 NICU beds are more likely to practice DCC, whereas Level 3 American Academy of Pediatrics NICUs, nonprofit owned hospitals, and teaching institutions were less likely to practice DCC (p < 0.001).Conclusion There are opportunities to implement quality improvement activities to increase DCC rates.
Keywords: delayed cord clamping; umbilical cord milking; preterm infants